Citizen Led Policing in the Digital Realm: Paedophile Hunters and Article 8 in the case of Sutherland v Her Majesty's Advocate. (Modern Law Review, 2022)
In Sutherland v Her Majesty's Advocate, the Supreme Court unanimously dismissed an appeal which argued that the use of communications obtained by a paedophile hunter group as evidence in criminal prosecution was a violation of Article 8 of the European Convention on Human Rights. The case raises fundamental questions of the scope of the right to private life as regards to the content of communications and the role played by private actors in the criminal justice process. This note argues that by limiting the protection of Article 8 to private communications which satisfy a contents‐based test, the Court has bypassed the Article 8(2) balancing test to the detriment of the due process rights of the accused. The note concludes that the decision opens up the prospect of the state circumventing the accused's Article 8 privacy rights by lending tacit approval to the proactive investigations of these private 'paedophile hunter' groups.